Effect of Atmospheric Pressure Plasma Treatment on the Lap-Shear Strength of Adhesive-Bonded Sheet Molding Compound Joints - Wang, Shuang; Min, Junying; Lin, Jianping; Sun, Chengcheng; Yang, Shanglu (Automotive innovation (Online), 2018)
Atmospheric pressure plasma treatment (APPT) technology was used herein to treat sheet molding compound (SMC) substrates to increase the lap-shear strength of adhesive-bonded SMC joints. Further, the mechanisms behind the lap-shear strength improvements in APPT-treated adhesive-bonded SMC joints were explored. A maximum lap-shear strength about three times that of the as-received SMC joints was achieved when the APPT distance was set to 20 mm. The surface roughness, which exhibited little benefit to the lap-shear strength, was determined to not be the primary reason for the increase in lap-shear strength. Specifically, X-ray photoelectron spectra revealed that an increased amount of O-containing groups (i.e., C–O–H, C–O–C, H–O–C=O or R–O–C=O) following APPT contributed to the improved lap-shear strength. In addition, the surface free energy increased significantly after APPT, which improved the lap-shear strength of the adhesive-bonded SMC joints. Compared to the change of surface morphology, the changes in both the surface chemical property and surface free energy played larger roles in increasing the lap-shear strength of APPT-treated SMC joints.